COMPUTATIONAL AND EXPERIMENTAL ASSESSMENT OF TURBULENCE STIMULATION ON FLOW INDUCED MOTION OF CIRCULAR CYLINDER - Kinaci, Omer Kemal; Lakka, Sami; Sun, Hai; Bernitsas, Michael M. (AMER SOC MECHANICAL ENGINEERS, 2015)
In the Marine Renewable Energy Laboratory (MRELab) of the University of Michigan, Flow Induced Motion (FEVI) is studied as a means to convert marine hydrokinetic energy to electricity using the VIVACE energy harvester [1-4]. Turbulence stimulation in the form of sand-strips, referred to as Passive Turbulence Control (PTC), were added to oscillating cylinders in 2008 [5]. PTC enabled VIVACE to harness hydrokinetic energy from currents/tides over the entire range of FIM including VIV and galloping. In 2011, the MRELab produced experimentally the PTC-to-FIM Map defining the induced cylinder motion based on the location of PTC [6]. In 2013, the robustness of the map was tested and dominant zones were identified [7]. Even though the PTC-to-FIM Map has become a powerful tool in inducing specific motions of circular cylinders, several parameters remain unexplored. Experiments, though the ultimate verification tool, are time consuming and hard to provide all needed information. A computational tool that could predict the FIM of a cylinder correctly would be invaluable to study the full parametric design space. A major side-benefit of PTC was the fact that PTC enabled computational fluid dynamic (CFD) simulations to generate results in good agreement with experiments by forcing the location of the separation point [8]. This valuable tool, along with experiments, is used in this paper to investigate PTC design parameters such as width and thickness and their impact on flow features with the intent of maximizing FIM and, thus, hydrokinetic energy conversion.
Keywords: VORTEX-INDUCED VIBRATIONS; SURFACE-ROUGHNESS; X 10(5); FREQUENCY; Engineering